A case of massive hemoptysis caused by immunoglobulin G4-related respiratory disease in adults: case report and review of literature - Mei, Chun-xia; Yue, Guo-long; Feng, Xia; Wu, Hai-qiao; Li, Jiong (Frontiers in Immunology, 2024)
Immunoglobulin G4-related disease (IgG4-RD) is an immune-mediated chronic fibro-inflammatory condition, that can involve multiple systems. Immunoglobulin G4-related respiratory disease (IgG4-RRD) is relatively rare, with non-specific clinical symptoms. Hemoptysis is a rare clinical symptom of IgG4-RRD, and cases of massive hemoptysis in adults have not been reported. We present here a rare case of massive hemoptysis caused by IgG4-RRD in adults and review relevant literature. An 84-year-old female presented with recurrent cough and blood-streaked sputum, progressing to massive hemoptysis. Her chest CT showed patchy lesions in the lungs, initially misdiagnosed as a tumor. Ultimately, a biopsy confirmed the diagnosis of IgG4-RRD. The patient was treated with prednisone combined with leflunomide, which controlled her condition and maintained remission. However, after 13 months without hemoptysis, she experienced intermittent hemoptysis followed by a massive episode. Increasing the prednisone dose and continuing leflunomide treatment controlled the condition once again, with no recurrence in the subsequent year of follow-up. In patients with IgG4-RRD, particularly those with hemoptysis, it is essential to remain vigilant for massive hemoptysis. Similarly, in patients with lung patch lesions and no evidence of a tumor on biopsy, IgG4-RRD should not be overlooked. Early diagnosis and timely treatment can improve the patient’s clinical prognosis.